Hospital Medicine : Perspectives, Practices and Professional Development - Habicht, Robert J.; Gulati, Mangla S. (Springer International Publishing : Imprint: Springer, 2017)
This practical resource provides hospitalists of all levels a comprehensive foundation for understanding the critical elements of hospital medicine. Beginning with an overview of the healthcare system, chapters provide relevant insights on management, regulations, evidence-based approaches, an awareness of safety and economic concerns and professional development skills. Perspectives on how hospitalist and hospital medicine teams can effectively engage this system to provide cost-effective, high-quality care are offered throughout this volume. With real-world guidance on the major tenets of hospital medicine, Hospital Medicine will serve as the definitive guide to a successful career in this rapidly evolving specialty.
Keywords: Medicine.; Health administration.; Practice of medicine.; elektronické knihy; electronic books